2021
DOI: 10.1126/science.abl8912
|View full text |Cite
|
Sign up to set email alerts
|

Protection against SARS-CoV-2 Beta variant in mRNA-1273 vaccine–boosted nonhuman primates

Abstract: Neutralizing antibody responses gradually wane against several variants of concern (VOCs) after vaccination with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine messenger RNA-1273 (mRNA-1273. We evaluated the immune responses in nonhuman primates that received a primary vaccination series of mRNA-1273 and were boosted about 6 months later with either homologous mRNA-1273 or heterologous mRNA-1273.b, which encompasses the spike sequence of the B.1.351 Beta variant. After boost, animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
95
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 45 publications
15
95
1
Order By: Relevance
“…Interestingly, vaccinated individuals who received an additional “booster” mRNA vaccine dose generated the most potent and cross-reactive antibody responses of any cohort tested, including individuals who recently received their primary series. The effect was similar to that observed following mRNA vaccine boosting in rhesus macaques ( Corbett et al, 2021 ). This substantial difference in Omicron cross-neutralization was surprising, given that two-dose and three-dose vaccine regimens elicited comparable levels of wild-type neutralization and because the immunogen was identical for all doses, which would be expected to elicit memory responses from the existing, strain-specific antibody repertoire.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, vaccinated individuals who received an additional “booster” mRNA vaccine dose generated the most potent and cross-reactive antibody responses of any cohort tested, including individuals who recently received their primary series. The effect was similar to that observed following mRNA vaccine boosting in rhesus macaques ( Corbett et al, 2021 ). This substantial difference in Omicron cross-neutralization was surprising, given that two-dose and three-dose vaccine regimens elicited comparable levels of wild-type neutralization and because the immunogen was identical for all doses, which would be expected to elicit memory responses from the existing, strain-specific antibody repertoire.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to the data with B.1.617.2, live virus neutralizing titers to B.1.351 showed a modest increase from week 24 to 48 (p = 0.0323). This observation, together with a difference in the kinetics of neutralizing titers to B.1.617.2 and B.1.351, suggests a change in serum epitope dominance and/or increased antibody affinity maturation, consistent with data showing a continued evolution of antibody responses induced by mRNA and adenovirus-vectored vaccines in NHPs and humans (Barouch et al, 2021;Corbett et al, 2021a;Gonzalez Lopez Ledesma et al, 2021).…”
Section: Resultssupporting
confidence: 76%
“…Recent studies in the United Kingdom, United States, and Qatar have shown a reduced efficacy of mRNA-based vaccines against asymptomatic and symptomatic, but not severe, B.1.617.2 infection (Bruxvoort et al, 2021;Chemaitelly et al, 2021;Lopez Bernal et al, 2021;Puranik et al, 2021;Tang et al, 2021). Antibody titers significantly decrease over a 6-month interval after the initial immunization series (Canaday et al, 2021;Corbett et al, 2021a;Levin et al, 2021), raising the concern that protection may wane. We and others reported that binding and neutralizing antibody titers in nonhuman primates (NHPs) and humans are key correlates of protection for mRNA and adenovirus-vectored COVID-19 vaccines (Corbett et al, 2021b;Gilbert et al, 2021;Khoury et al, 2021;Roozendaal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Through this strategy, we have produced wildtype SARS-CoV-2 spike ectodomain and subdomain probes allowing for the identification of potent neutralizing antibodies and nanobodies that target the receptor binding domain (RBD) or the N-terminal domain (NTD) of SARS-CoV-2 [1419], the characterization of antibody binding affinities and specificities, and the quantification of immune responses against spike and its subdomains in nonhuman primates to inform vaccine development [20, 21] and to find correlates of elicited responses with neutralization [22]. Moreover, with the rise of SARS-CoV-2 VOCs, we found that probes incorporating mutations defined by the variants could be helpful in the characterization of the impact of VOC mutations on vaccine effectiveness [2325].…”
Section: Introductionmentioning
confidence: 99%